2020
DOI: 10.4103/ijnmr.ijnmr_51_19
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dignity therapy on the quality of life of patients with cancer receiving palliative care

Abstract: Background: Patients with cancer deal with physical, psychosocial, spiritual, and existential problems that impact on their quality of life. This study aimed to assess the effect of dignity therapy on the quality of life of mentioned patients. Materials and Methods: In this quasi-experimental study, 50 patients with cancer hospitalized in a palliative care center in Tehran, Iran, in 2017-18 who fulfilled inclusion criteria were selected through convenience sampling. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
(37 reference statements)
0
8
0
2
Order By: Relevance
“…The important components and findings of final included articles are presented in Table 2 . Results of the study showed that included studies had a focus on different patients/participants including cancer,[ 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] hemodialysis,[ 45 ] heart failure,[ 46 47 ] chronic disease,[ 48 ] chronic pain,[ 49 ] and with anonymous groups. [ 50 51 52 53 54 55 ] Several provinces/cities were engaged in the studies including Tehran,[ 12 13 14 15 17 20 21 24 25 26 29 30 31 32 33 34 35 37 39 40 41 42 43 48 , 51 , 52 Isfahan,[ 22 27 28 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The important components and findings of final included articles are presented in Table 2 . Results of the study showed that included studies had a focus on different patients/participants including cancer,[ 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ] hemodialysis,[ 45 ] heart failure,[ 46 47 ] chronic disease,[ 48 ] chronic pain,[ 49 ] and with anonymous groups. [ 50 51 52 53 54 55 ] Several provinces/cities were engaged in the studies including Tehran,[ 12 13 14 15 17 20 21 24 25 26 29 30 31 32 33 34 35 37 39 40 41 42 43 48 , 51 , 52 Isfahan,[ 22 27 28 …”
Section: Resultsmentioning
confidence: 99%
“…[ 50 51 52 53 54 55 ] Several provinces/cities were engaged in the studies including Tehran,[ 12 13 14 15 17 20 21 24 25 26 29 30 31 32 33 34 35 37 39 40 41 42 43 48 , 51 , 52 Isfahan,[ 22 27 28 38 55 ] Kerman,[ 45 53 ] Tabriz,[ 16 36 ] Mashhad,[ 18 19 ] Yasouj,[ 44 ] Gorgan,[ 49 ] Neyshabour,[ 50 ] Jiroft,[ 46 47 ] Meybod/Ardakan,[ 54 ] Gorgan/Gonabad. [ 23 ] Majority of studies had quantitative approach, including interventional,[ 17 18 19 22 23 29 31 33 35 44 47 49 54 ] descriptive,[ 20 39 41 42 50 53 ] and correlational-analytical. [ 37 45 46 51 ] This was then followed by qualitative[ 12…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations